Biostratigraphy and geography of the Ordovician-Silurian Lungmachi black shales in South China - Fan JunXuan (樊隽轩); Melchin, Michael J.; Chen Xu (陈旭); Wang Yi (王怿); Zhang YuanDong (张元动); Chen Qing (陈清); Chi ZhaoLi; Chen Feng (Science China Earth Sciences, 2011)
Based on the new material of seven Ordovician-Silurian boundary sections investigated recently, together with previously published data, we analyze the temporal and spatial distributions of the Lungmachi black shales, a key petroleum source bed widely distributed in South China. The Lungmachi black shales range in age from the Normalograptus persculptus Biozone of the uppermost Ordovician to the Spirograptus guerichi Biozone of the lower Telychian, and ten graptolite biozones can be recognized within this unit. The basal and upper contacts of the Lungmachi black shales are diachronous. The basal contact ranges from the N. persculptus to the C. cyphus biozones, a span of five graptolite biozones over two stages. The upper contact ranges from the D. pectinatus-M. argenteus Biozone to the Spirograptus guerichi Biozone, which spans four graptolite biozones over two stages. The Yichang Uplift resulted in the formation of the Hunan-Hubei Submarine High in the border area of Hubei, Hunan, and Chongqing. This is supported by a break in sedimentation in this area spanning all or part of the Hirnantian, and in many areas extending into the underlying Katian and overlying Rhuddanian. Comparison of the distribution of the Katian to Rhuddanian strata in this area indicates a growth and subsequent reduction in area of the Hunan-Hubei Submarine High particularly in the Hirnantian to early Rhuddanian. This may partly represent the influence of the process of formation and melting of ice sheet in Ordovician South Pole and consequent sea level change.